Profil Kehidupan Anak Jalanan di Kota Pematangsiantar - Lubis, Hotland; Hodriani, Hodriani (Universitas Medan Area, 2016)
This study aims to find out about the village government performance, especially in terms of cooperation, discipline, creativity, responsibility as well as identify obstacles and barriers to the performance of the Government of the District Rural Middle Bandar Khalifah Bedagai Serdang. Issues to be raised in this study are: (1) the performance of the Government of the District Rural Middle Bandar Khalifah Bedagai Serdang, (2) Barriers, constraints and performance tasks Village Government, (3) prevention efforts and performance bottleneck tasks Village Government Central City Subdistrict Bandar Khalifah Bedagai Serdang. This study uses a qualitative description as a method of data analysis that takes research location in Airport Village Head Office Central District of Bandar Khalifah Bedagai Serdang. Source of data in this study is the Village Head and local villagers. Data were collected by interviews and documentation. These results indicate that the performance of the Government of the District Rural Middle Bandar Khalifah Bedagai Serdang in terms of the gobernance process that emphasizes teamwork, discipline, creativity and responbilities have not been able provide maximum services that fit the needs of the community.